2022
DOI: 10.3390/vaccines10081171
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients with Pustular Psoriasis: A Single-Center Retrospective Observational Study

Abstract: Clinical and epidemiologic data on pustular psoriasis are scarce. To investigate the phenotypes of pustular psoriasis and the patients’ characteristics observed in a real-life retrospective observational study. The number of incident cases of pustular psoriasis registered in the period 2005–2021 was retrieved from the electronic medical records of the University Hospital of Verona. One hundred and forty cases of pustular psoriasis were collected. Ninety-one out of 140 patients (65%) were females, with a median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…17 -18 In total, 76.0% of patients in our study had a history of PsV, with a previously reported proportion of 10.7% to 85.5%. 12,[14][15][16][17][18][19][20] Studies have shown that female patients seem to be more common in GPP −PsV than GPP +PsV , 13,[17][18] which is consistent with our results. However, there was no statistically significant difference in the sex composition between the 2 groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…17 -18 In total, 76.0% of patients in our study had a history of PsV, with a previously reported proportion of 10.7% to 85.5%. 12,[14][15][16][17][18][19][20] Studies have shown that female patients seem to be more common in GPP −PsV than GPP +PsV , 13,[17][18] which is consistent with our results. However, there was no statistically significant difference in the sex composition between the 2 groups.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have suggested that female patients seem to be more common in GPP [11][12][13][14][15][16] ; however, the data vary according to geographical and racial differences (Table 4). Our study included more male than female patients (96/83), which is similar to the study performed by Ohata et al 18 (53/49).…”
Section: Discussionmentioning
confidence: 99%
“…Comorbid diseases of patients with ACH were not different from those with GPP in which metabolic comorbidities were frequent 3,48 . Psoriatic arthritis occurs in 20.5%–36.4% of patients with ACH 3,48,49 . From our review (Table 1), the frequency of concomitant plaque psoriasis in patients with ACH (6.5%–46.2%) 3,45,48,49 appears lower than that of patients with GPP (31.3%–78%) 8,10,43,44 …”
Section: Introductionmentioning
confidence: 63%
“…3,48 Psoriatic arthritis occurs in 20.5%-36.4% of patients with ACH. 3,48,49 From our review (Table 1), the frequency of concomitant plaque psoriasis in patients with ACH (6.5%-46.2%) 3,45,48,49 appears lower than that of patients with GPP (31.3%-78%). 8,10,43,44…”
Section: Ach Alone and Predominate Achmentioning
confidence: 75%
See 1 more Smart Citation